2018
DOI: 10.5897/ajb2017.16338
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological diversity of rhizobia nodulating pigeon pea (Cajanus cajan L. Millsp.) growing in Ethiopia

Abstract: Pigeon pea (Cajanus cajan (L.) Millsp.) is an important protein source grown in several tropical and subtropical countries, and is considered a multi-purpose plant that is resistant to the conditions where drought and salinity is a common phenomenon. The aim of this study was to evaluate the diversity of rhizobial isolates obtained from root nodules of pigeon pea plants grown in central and southern Ethiopia. A total of 116 nitrogen-fixing rhizobial strains were isolated. The bacterial isolates were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Isolates HUCR-3 (South Ari) and HUCR-7 (Humbo, Wolaita) showed the highest tolerance to salt concentration up to 6% NaCl (Table 4). A report by Degefu et al (2018) also indicated that rhizobia isolates collected from southern Ethiopia were able to tolerate the highest salt concentration of 5.5%. This ability can make them highly competitive in colonizing the rhizosphere and fixing nitrogen in salinity affected soils.…”
Section: Salt Tolerancementioning
confidence: 93%
See 3 more Smart Citations
“…Isolates HUCR-3 (South Ari) and HUCR-7 (Humbo, Wolaita) showed the highest tolerance to salt concentration up to 6% NaCl (Table 4). A report by Degefu et al (2018) also indicated that rhizobia isolates collected from southern Ethiopia were able to tolerate the highest salt concentration of 5.5%. This ability can make them highly competitive in colonizing the rhizosphere and fixing nitrogen in salinity affected soils.…”
Section: Salt Tolerancementioning
confidence: 93%
“…Besides, the isolates can be used as potential inoculants to realize higher yields under a wide range of environmental conditions. A study by Degefu et al (2018) also reported that rhizobial isolates which tolerated a broader range of temperature are often used as inoculant and/or for production of biofertilizer under wider ecological conditions.…”
Section: Temperature Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…is study focused on providing information on the current prospects of pigeon pea adaptation and production potential in Ethiopia. It is expected to provide information regarding whether the farmers will cultivate more or reduce the land allotted to pigeon pea production [16]. Although there is no systematic scoring and a national database, it is distributed all over the geographies in the North (Wollo), South East (Bale), Southern Region, Western regions, and central parts of Ethiopia, growing in patches and intercropped [17].…”
Section: Introductionmentioning
confidence: 99%